Production of Natural Composite with Alkaline Treatment Using Empty Fruit Bunch Ash Extract Solution (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Empty fruit bunch (EFB) is one of waste from oil palm mill which is abundantly available and sustainable but not optimally utilized. EFB fiber can be used as composite reinforcement. EFB fiber have a specific strength, low density, biodegradable and low cost. The combustion of EFB generated ash which is rich in potassium. Hydrolysis of EFB ash creates base solution that can be utilized in alkaline treatment process to increase the mechanical properties of natural composite. Objective of this research is to study the effect of alkaline treatment using EFB ash extract solution, to obtain the optimum process condition in alkaline treatment process, to characterize tensile strength, flexural strength and water absorption of the composite. Fiber with various length 1, 2 and 3 cm are soaked using EFB ash extract solution with various concentration of the extract solution 5, 10 and 15%wt for 12, 24 and 36 hours respectively. Tensile strength is tested by JIS K6781. Flexural strength is tested by ASTM D790 and ASTM D570 for water absorption testing. Design experiment using response surface method (RSM) used for response optimizing. Tensile strength resulted is increase with increasing fiber length and increasing concentration of the EFB ash extract solution. Longer soaking time caused brittleness in fiber so that the tensile strength is decrease. Flexural strength is increase with increasing fiber length. Increasing concentration of the EFB ash extract solution and longer soaking time decrease the flexural strength.Keywords: alkaline treatment; composite; EFB ash extract solution; EFB fiber; flexural strength; response surface method; tensile strength; water absorption.